Inferior Outcomes of EU Versus US Patients Treated With CD19 CAR-T for Relapsed/Refractory Large B-cell Lymphoma: Association With Differences in Tumor Burden, Systemic Inflammation, Bridging Therapy Utilization, and CAR-T Product Use - Veit Bücklein; Ariel Perez; Kai Rejeski; Gloria Iacoboni; Vindi Jurinovic; Udo Holtick; Olaf Penack; Soraya Kharboutli; Viktoria Blumenberg; Josephine Ackermann; Lisa Frölich; Grace Johnson; et al. (HemaSphere, 2023)
Real-world evidence suggests a trend toward inferior survival of patients receiving CD19 chimeric antigen receptor (CAR) T-cell therapy in Europe (EU) and with tisagenlecleucel. The underlying logistic, patient- and disease-related reasons for these discrepancies remain poorly understood. In this multicenter retrospective observational study, we studied the patient-individual journey from CAR-T indication to infusion, baseline features, and survival outcomes in 374 patients treated with tisagenlecleucel (tisa-cel) or axicabtagene-ciloleucel (axi-cel) in EU and the United States (US). Compared with US patients, EU patients had prolonged indication-to-infusion intervals (66 versus 50 d; P < 0.001) and more commonly received intermediary therapies (holding and/or bridging therapy, 94% in EU versus 74% in US; P < 0.001). Baseline lactate dehydrogenase (LDH) (median 321 versus 271 U/L; P = 0.02) and ferritin levels (675 versus 425 ng/mL; P = 0.004) were significantly elevated in the EU cohort. Overall, we observed inferior survival in EU patients (median progression-free survival [PFS] 3.1 versus 9.2 months in US; P < 0.001) and with tisa-cel (3.2 versus 9.2 months with axi-cel; P < 0.001). On multivariate Lasso modeling, nonresponse to bridging, elevated ferritin, and increased C-reactive protein represented independent risks for treatment failure. Weighing these variables into a patient-individual risk balancer (high risk [HR] balancer), we found higher levels in EU versus US and tisa-cel versus axi-cel cohorts. Notably, superior PFS with axi-cel was exclusively evident in patients at low risk for progression (according to the HR balancer), but not in high-risk patients. These data demonstrate that inferior survival outcomes in EU patients are associated with longer time-to-infusion intervals, higher tumor burden/LDH levels, increased systemic inflammatory markers, and CAR-T product use.